Pengaruh Self-Esteem terhadap Social-Loafing dengan Academic Honesty sebagai Mediator - Darma Sena; Edy Purwanto; Ali Murtadho (Kuras Institute, 2022)
This research aims to analyze the relationship of self-esteem with social loafing through academic honesty as a mediator variable. We involved 232 junior high school students in Banda Aceh which selected using cluster random sampling. This study uses a scale of psychological adaptation and questionnaire as instruments. The results showed that self-esteem had a significant association with social loafing with a value of (β = -0.436 and significantly at the level of p < 0.05). Academic honesty also has a significant relationship with social loafing with values (β = -0.264 and significantly at the level of p < 0.05). Self-esteem is significantly related to academic honesty with values (β = 0.992 and significantly at the level of p < 0.05). Research indicates that academic honesty is a mediator in the relationship between self-esteem and social loafing. Students with high self-esteem tend to have high academic honesty. This is expected to reduce social loafing behavior in students.